Применение систолической системы на основе метода моментов для усовершенствования дискретного преобразования Хартли - Горюшкина, А. Е.; Семенов, Сергей Геннадьевич (Харківський національний університет Повітряних Сил ім. Івана Кожедуба, 2016)
Определена целесообразность усовершенствования дискретного преобразования Хартли для решения задач оперативного сжатия данных. Построен систолический массив вычисления дискретного преобразования Хартли. Усовершенствовано дискретное преобразование Хартли на основе метода моментов. Сделаны выводы о возможностях применения дискретного преобразования Хартли.

Expedience of improvement of discrete transformation is certain Khartli for the decision of tasks of operative compression of data. The systole array of calculation of discrete transformation is built Khartli. Discrete transformation is improved Khartli on the basis of method of moments. Conclusions are done about possibilities of application of discrete transformation Khartli.
The use of the systolic system based on the method of moments to improve the discrete Hartley transform
Keywords: линейный массив; систолический массив; сжатие цифровых данных; преобразование Фурье; linear array; systole array